Integrando dimensiones para la comprensión del proceso de abandono de los sistemas de andenería de la comunidad campesina de San Juan de Iris, subcuenca Santa Eulalia, Huarochirí - Yakabi Bedriñana, Katiusca Susana (2017)
The present research, "Integrating dimensions for the understanding of the abandonment process of highland terracing systems of the rural community of San Juan de Iris, Santa Eulalia sub–basin, Huarochirí" has as general objective to analyze articulately physical, social, economic, productive and institutional factors that lead to the abandonment of the highland terracing systems. The integrated understanding of the problematic is the base to propose recommendations for a productive system that contributes to the sustainable development of the community, as well as to the conservation and enhancement of its agricultural terraces. In order to achieve this objective, the methodology was organized in three phases in which instruments of different sciences, such as soil science, geography and anthropology, were applied to collect qualitative and quantitative information. The first phase consisted in a revision of bibliographical, statistical and cartographical information, as a basis for the research approach and the methodology itself. In the fieldwork, soil samples of the platforms were taken, and quantitative information and perception were collected through surveys, interviews and a workshop. Finally, in the third phase, precipitation data was acquired with the subsequent calculation of interannual variability, the physical and chemical properties of the sampled soil were analyzed and interpreted, the information obtained from the surveys, interviews and workshop were systematized and the analysis was made. Applying a participatory approach, the rural community of San Juan de Iris was involved throughout the investigation to be an active part of the process. The highland terracing system studied belongs to the rural community of San Juan de Iris, in the district of the same name, located in left margin of the upper part of the Santa Eulalia sub– basin, Huarochirí, in the Andean zone of Lima. In the 1990s, this community was benefited from a rehabilitation experience of the National Program for Watershed Management and Soil Conservation (PRONAMACHCS, for its acronym in Spanish); nevertheless, at the present time, 59.7% of its terracing systems are in a situation of abandonment. For this reason, this community was chosen as the case study. Field verification carried out by PRONAMACHCS indicates that the abandonment of terraces in San Juan de Iris was in an 80% due to the water deficit (natural factor) and 20% to the migration from the countryside to the city (social factor). However, the Andean rural reality is much more complex; therefore, physical, institutional, economic-productive, and social dimensions of the territory were explored in the research. The main drivers of the abandonment of the San Juan de Iris terracing systems were the search for generating economic power (economic-productive factor); migration of young people and adults (social factor); perception of decrease and lack of water resources (physical-natural factor); change in the regime of the land tenure (institutional factor); and dependence on projects and programs of external agents (socio-institutional factor). With the main drivers of the abandonment process of the terracing systems identified, it is possible to propose the actions in order to eliminate the causes of the problem. Otherwise, the consequences derived from the abandonment process will intensify: underutilization of the soil resource and food insecurity; increasing pressure on the natural pasture ecosystem that leads to a risk in the profitability of livestock; loss of ancestral technique and knowledge; and lack of initiative for the conservation of their agricultural terraces and for the development of the community. As a solution strategy is proposed to position the highland terraces as key element in the development of the rural community of San Juan de Iris. For this, the agriculture on terraces must respond to the expectations of the community, so that by their own and shared initiative, they will include this productive and cultural resource in their vision of development.